Synthesis and crystallographic characterization of N-allyl-N-benzyl-4-methylbenzenesulfonamide - Stenfors, Brock Anton; Ngassa, Felix Nyuangem (European Journal of Chemistry, 2020)
N-Benzyl-4-methylbenzenesulfonamides were prepared via a two-step synthetic process involving the treatment of 4-methylbenzenesulfonyl chloride with a primary amine to give the corresponding 4-methylbenzenesulfonamide. Benzylation of the sulfonamide affords the substituted N-benzyl-4-methylbenzenesulfonamides. The similarities between the two steps of synthesis lend credence to the development of a one-pot synthesis of substituted N-benzyl-4-methylbenzenesulfonamides from 4-methylbenzenesulfonyl chloride. This method was applied to the synthesis of N-allyl-N-benzyl-4-methylbenzenesulfonamide and characterized through spectroscopic and crystallographic means. The crystal structure of N-allyl-N-benzyl-4-methylbenzenesulfonamide was obtained by single-crystal X-ray diffraction. The crystal structure reveals an orthorhombic Pna21 space group with cell parameters a = 18.6919 (18) Å, b = 10.5612 (10) Å, c = 8.1065 (8) Å, V = 1600.3 (3) Å3 and Z = 4, T = 173.15 K, μ(MoKα) = 0.206 mm-1, Dcalc = 1.251 g/cm3, 14455 reflections measured (4.36° ≤ 2Θ ≤ 54.96°), 3619 unique (Rint = 0.0439, Rsigma = 0.0429) which were used in all calculations. The final R1 was 0.0428 (I > 2σ(I)) and wR2 was 0.1079 (all data). Molecules are linked through C-H···N hydrogen bonds and C-H···π interactions.